BETWIXT DEMOCRACY, OCHLOCRACY AND THE LIKE: INTERROGATING CONTRADICTIONS OF THE LIBERAL DEMOCRATIC ORDER - Okoli, Al Chukwuma; Ibrahim, Abdulrasheed Adam (European Scientific Journal, ESJ, 2014)
This paper explores the contradictory character of liberal democracy with particular reference to its contemporary manifestations. By way of qualitative analysis of secondary sources, the paper posits that the practice of democracy has been fraught with contradictions and that such contradictions (such as mobocracy, civil licentiousness and restiveness) have engendered conditions that tend to negate the essence and purpose of the practice. From the perspective of the Arab Spring and Ukrainian crisis, the paper contends that the contradictions of democracy, as exemplified in mob rule and civil restiveness, have belied the assumption that liberal democracy is the ultimate socio-political order. The paper submits that the prospect of resolving the contradictions of liberal democracy lies in the return to republicanism which depicts the original intent of the democratic concept and practice.